Case report: Isoflurane therapy in a case of status asthmaticus requiring extracorporeal membrane oxygenation - Gill, Brendan; Bartock, Jason L.; Damuth, Emily; Puri, Nitin; Green, Adam (Frontiers in Medicine, 2022)
Volatile anesthetics have been described as a rescue therapy for patients with refractory status asthmaticus (SA), and the use of isoflurane for this indication has been reported since the 1980s1. Much of the literature reports good outcomes when inhaled isoflurane is used as a rescue therapy for patients for refractory SA2. Venovenous (VV) extracorporeal membrane oxygenation (ECMO) is a mode of mechanical circulatory support that is usually employed as a potentially lifesaving intervention in patients who have high risk of mortality3, primarily for underlying pulmonary pathology. VV ECMO is usually only considered in cases where patients gas exchange cannot be satisfactorily maintained by conventional therapy and mechanical ventilation strategies4. We report the novel use of isoflurane delivered systemically as treatment for severe refractory SA in a patient on VV ECMO. A 51-year-old male with a history of asthma was transferred from another institution for management of severe SA. He was intubated at the referring hospital after failing non-invasive ventilation. Initial arterial blood gas (ABG) showed pH 7.21, partial pressure of carbon dioxide (PCO2) >95mmHg, and partial pressure of oxygen (PaO2) 60mmHg. VV ECMO was initiated on hospital day (HD) 1 due to refractory respiratory acidosis. After ECMO initiation, acid-base status improved, however, severe bronchospasm persisted and intrinsic positive end expiratory pressure (PEEP) was measured at 18cm H2O. Systemic paralysis was employed, respiratory rate (RR) was reduced to 4 breaths per minute. This degree of bronchospasm did not allow for ECMO weaning. On HD 5, the patient received systemic isoflurane via the ECMO circuit for 20 hours. The following morning, intrinsic PEEP was 4cm H2O, and wheezing improved. He was decannulated from VV ECMO on HD 10 and extubated on HD 17. Inhaled isoflurane therapy in patients on VV ECMO for refractory SA has shown good results5-6, but requires delivery of the medication via anesthesia ventilators. Our case highlights an effective alternative, systemic delivery of anesthetic via the ECMO circuit, as it is often difficult and dangerous to transport these patients to the operating room or have an intensive care unit room adjusted to accommodate an anesthesia ventilator.